2008
DOI: 10.1007/s00128-008-9542-2
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Distribution, and Characterization of Polycyclic Aromatic Hydrocarbons in Soil in Linfen, China

Abstract: A total of 10 surface soil samples representing the entire area of Linfen City were collected and analyzed for the presence of 16 polycyclic aromatic hydrocarbons. The total polycyclic aromatic hydrocarbon concentration ranged from 1.1 to 63.7 lg g -1 . Analysis of the sources of contamination revealed that polycyclic aromatic hydrocarbons in the soil were derived from combustion sources. Specifically, the primary source of polycyclic aromatic hydrocarbons was coal combustion, but the samples were also effecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… ND: not detected; SD: standard deviation; CV: coefficient of variation; AC: acceptable concentrations [ 55 ]; Σ16PAHs: the sum of sixteen individual PAHs; Σ7CPAHs: the total of seven carcinogenic PAHs including BaA, Chy, BbF, BkF, BaP, DBA, and InP; ΣCOMB: the sum of major combustion-specific compounds containing Fla, Pyr, BaA, Chy, BbF, BkF, BaP, BghiP, and InP [ 44 , 56 , 57 ]; LMWPAHs: the total of low molecular weight PAHs, i.e, NaP, Acy, Ace, Flu, Phe, and Ant; HMWPAHs: the sum of high molecular weight PAHs, i.e, Fla, Pyr, BaA, Chy, BbF, BkF, BaP, DBA, BghiP, and InP. …”
Section: Figurementioning
confidence: 99%
“… ND: not detected; SD: standard deviation; CV: coefficient of variation; AC: acceptable concentrations [ 55 ]; Σ16PAHs: the sum of sixteen individual PAHs; Σ7CPAHs: the total of seven carcinogenic PAHs including BaA, Chy, BbF, BkF, BaP, DBA, and InP; ΣCOMB: the sum of major combustion-specific compounds containing Fla, Pyr, BaA, Chy, BbF, BkF, BaP, BghiP, and InP [ 44 , 56 , 57 ]; LMWPAHs: the total of low molecular weight PAHs, i.e, NaP, Acy, Ace, Flu, Phe, and Ant; HMWPAHs: the sum of high molecular weight PAHs, i.e, Fla, Pyr, BaA, Chy, BbF, BkF, BaP, DBA, BghiP, and InP. …”
Section: Figurementioning
confidence: 99%
“…Some studies have indicated a major source of LPAHs to be gaseous atmospheric deposition in surface marine waters (Tsapakis et al, 2006;Castro-Jiménez et al, 2012). Moreover, many studies showed that the predominance of LPAHs indicate a petrogenic contamination, such as crude oil or unburned petroleum and its products; and the predominance of HPAHs indicate a pyrogenic source, such as incomplete combustion of coal and petroleum (Xu et al, 2007;Fu et al, 2009). Therefore, PAHs in the Haikou Bay may primarily come from atmospheric deposition and petrogenic sources.…”
Section: Introductionmentioning
confidence: 96%
“…Before extraction, 2-FBP and TCMX were added to the accurately weighed soil samples as surrogate standards for PAHs, OCPs and PCBs individually, and balanced at desiccator for 2 hours. Cleanup of PAHs, OCPs and PCBs individually followed the modified methods of our previous reports (Fu et al, 2008a(Fu et al, , 2008b(Fu et al, , 2009a, and the detailed processes are described in SM.…”
Section: Extraction and Cleanupmentioning
confidence: 99%
“…The detailed analytic conditions for PAHs, OCPs and PCBs followed those described in our previous reports (Fu et al, 2008a(Fu et al, , 2008b(Fu et al, , 2009aYuan et al, 2014) with a 30 m DB-5MS (30 m × 0.25 mm i.d., 0.25 μm film thickness) capillary column. As shown in Table S1 (in SM), 16 PAHs, 23 OCPs and 125 PCBs were detected.…”
Section: Analysis and Quality Controlmentioning
confidence: 99%